2020
DOI: 10.1002/agj2.20052
|View full text |Cite
|
Sign up to set email alerts
|

Drip irrigation with organic fertilizer application improved soil quality and fruit yield

Abstract: Irrigation and fertilization management are important for controlling agricultural soil salinity and increasing productivity in extremely arid regions. The objective of this research was to evaluate the effects of long‐term drip irrigation and organic fertilizer application on soil salinity, fruit quality and yield of jujube [Ziziphus ziziphus (L.) Karst]. We established a 7‐yr field experiment in a desert‐oasis area in Northwest China. Six treatments were performed: CK (conventional irrigation, no fertilizer)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 67 publications
(91 reference statements)
1
9
0
Order By: Relevance
“…Our findings are consistent with previous research [56]. Increases in macronutrient and micronutrient contents in the irrigated and fertilized plots were probably due to the combined effect of irrigation and fertilizer, which might have promoted the conversion of crop residues to SOC and growth of the microbial population [55,57]. Overall, the short-term application of a combination of irrigation and fertilizer could promote microbial activity, SOC buildup and nutritional status of cactus pear.…”
Section: Change In Soil Properties and Nutrient Statussupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with previous research [56]. Increases in macronutrient and micronutrient contents in the irrigated and fertilized plots were probably due to the combined effect of irrigation and fertilizer, which might have promoted the conversion of crop residues to SOC and growth of the microbial population [55,57]. Overall, the short-term application of a combination of irrigation and fertilizer could promote microbial activity, SOC buildup and nutritional status of cactus pear.…”
Section: Change In Soil Properties and Nutrient Statussupporting
confidence: 91%
“…In the current study, the decrease in soil pH might be related to the soil conditions or to the acidifying effect of manure application [53,54]. In a short-term study (7 years), Li et al [55] observed a 10% decrease in soil pH and a 44.19% increase in SOC under drip irrigation with organic fertilizer treatment compared to before the treatments commenced.…”
Section: Change In Soil Properties and Nutrient Statusmentioning
confidence: 61%
“…The differences for all outcomes are 12.8, 11.8, and 23.5% higher for per-capita outcomes of house, food, and asset, respectively. This may be due to the high humidity and rainfall pattern in the southern region as organic manure requires adequate water in activating essential nutrients, controlling salinity (Li et al, 2020).…”
Section: Heterogeneous Impact Of Adoption Of Organic Fertilizersmentioning
confidence: 99%
“…F. Li et al. (2020) conducted a 7‐yr study on drip irrigation and organic fertigation. They conclude that organic fertigation with drip irrigation is the best strategy for obtaining higher productivity and improving fruit quality in arid zones for optimum market crop production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drip irrigation and organic fertigation are gaining momentum in saline‐sodic soils, particularly under low‐rainfall areas. They contribute to soil and food quality (F. Li et al., 2020). In addition, liquid biofertilizers are more easily absorbed by the soil than solids and produce crop yields comparable to conventional farming (de Lima et al., 2020).…”
Section: Introductionmentioning
confidence: 99%